A CROSS-SECTIONAL STUDY OF SURGICAL SMOKE INHALATION, ITS HAZARDS AND PREVENTION AMONG PAEDIATRIC SURGICAL RESIDENTS IN PAKISTAN - Habib, Murad; Chaudhary, Muhammad Amjad (Journal of Ayub Medical College Abbottabad, 2023)
Background: For thousands of years human beings have been using heat as a source of ligature and to treat the wound either it’s from the trauma or fought in the wars. In 1854 an imminent surgeon Albrecht Theodor Middendorf published a paper on the application of electrocautery in surgical operations. The objective of the study was to analyze the hazards of surgical smoke inhalation in Paediatric Surgery residents and to create awareness of its signs and symptoms, risk factors and utilizing preventive measures. Methods: A Cross-sectional study was conducted involving all the Paediatric Surgery residents enrolled on a supervised training program in Pakistan between 1st July 2022 to 30th June 2023 at all the tertiary care hospitals in Pakistan. Their socio-demographic, academic data, signs and symptoms and risk factors were calculated. Data was analyzed with descriptive and comparative analysis using SPSS. A Pearson contingency coefficient is used to determine the association between categorical variables. Results: Our study included all the Paediatric Surgery residents in Pakistan n=155 over a span of one year starting from July 1st 2022 to June 30th 2023. N=75 (48.4%) were males and n=80 (52.6%) were female residents. Their mean age was 29.5 years±4 (SD). 41% of the residents were from Khyber Teaching Hospital, 32% from Children’s Hospital, 14% from National Institute of Child Health Karachi, 9.8% from Children’s Hospital Islamabad (PIMS) and 5.2% from Lady Reading Hospital Peshawar. N=135 (87.1%) of the residents used electrocautery while performing the surgery (p=0.006). N=121 (78.1%) were aware of its hazards (p=0.341). 90% think they are at an increased risk (p=0.032). Most of them (84.6%) wear a surgical mask while only (64%) wear protective equipment (p=0.321). Think they are at an increased risk of cancers (83.9%) (p=0.002) and should be screened (93.7%) (p=0.343). Conclusion: Paediatric surgery residents are at an increased risk of surgical smoke inhalation, pointing to the emerging need to adopt protective measures by creating awareness, and utilizing health safety checklists and smoke evacuation mechanisms in operation rooms. All residents should seek knowledge on the subject and use personal protective equipment for less harmful effects on their health.